Camiones Hyundai: desarrollo y reposicionamiento en el mercado automotriz peruano - Carbajal Díaz, Edilberto Rafael (2021)
The present work analyzes the situation of the Hyundai Trucks Brand developing alternative solutions to develop and reposition it in the Peruvian automotive market. Hyundai trucks are marketed in Peru since 2007 through its Authorized Dealer Automotores Gildemeister S.A. A brand present in the light segment where it maintained the leadership that has gradually been declining due to the lack of renewal of the reference models in the same, new alternatives of the competition basically of Japanese brands and a communication that does not pump in the target market. Unlike other competing brands, Hyundai trucks concentrated on a segment of the total market (segmentation established by the Peruvian Automotive Association) where 4 segments are defined according to the load range and weights. The above became a serious risk for not participating in the main segments but reduced to a single segment, so it becomes urgent to expand the presence of the brand with larger tonnage models. The present study show us the decisions taken and those that are aimed at giving validity and development to the brand, developing the sales channels of the business model of Automotores Gildemeister SA, by offering greater value, differentiation, diversification, personality and repositioning achievement to be in the intention of the user client in each purchase decision, with the aim of presenting transport solutions in the segments of greater market share that ensure viability to the brand, income and value generation that the shareholders of the company demand.